Building a meal : from molecular gastronomy to culinary constructivism - This, Hervé (Arts and traditions of the table., 2009)
Considering six bistro favorites, Hervé This isolates the exact chemical properties that tickle our senses and stimulate our appetites. More important, he identifies methods of culinary construction that appeal to our memories, intelligence, and creativity.